Угадай-ка: [для чтения взрослыми детям] / худож. С. Самсоненко - Самсоненко С. (Тебе, малыш !, 2015)
Экземпляры: ф.13 (2018) / Инвентарный номер: 54449 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: У 24 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6